(untitled) (Proceedings of International Conference on Modern Science and Scientific Studies, 2024)
This article explores the transformative impact of technology on the lives of disabled individuals, emphasizing how innovations enhance accessibility, independence, and overall quality of life. Assistive technologies, such as screen readers, voice recognition software, and adaptive devices, empower users by facilitating communication, mobility, and daily activities. The integration of smart home systems further promotes autonomy, allowing individuals to control their environments with ease. Additionally, advancements in virtual and augmented reality provide immersive experiences that enhance social interaction and engagement. By highlighting case studies and user testimonials, this article demonstrates that technology not only addresses specific challenges faced by disabled people but also fosters inclusion and empowerment in society. Ultimately, embracing these innovations is essential for creating a more equitable world for all individuals, regardless of their abilities.